COPING BEHAVIOR OF JOHN NASH IN RON HOWARD'S A BEAUTIFUL MIND MOVIE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - KARYAWATI, NANA APRIANA (2011)
The object of the research is the movie entitled A Beautiful Mind by Ron Howard. The study gives focus on Alfred Adler's individual psychological approach as reflected in A Beautiful Mind by Ron Howard. The aim of the study is finding the structural elements and to reveal the major character's inferiority feeling based on individual psychological perspective. The study belongs to a qualitative study. In this method, the researcher uses two data sources namely primary and secondary data. The primary data source and object of study is the movie A Beautiful Mind itself, meanwhile the secondary is any reference related the study. The technique of data analysis in this study is descriptive to make an interpretation of the text and content analysis using deductive and inductive method. The result of the study shows the following conclusion. The inferiority feeling of life influences the major character John Nash's personality development in avoiding pain and finding pleasure. All his efforts are done to cheer up himself and his family in order to carry on his life and try to clear an anxiety in his life. Even though he has to cope with his own life, he can manage to take care of his friends. He is strong man. He must strive for success and superiority. He has gone through a lot of problems, but he can survive his difficulties. His inferiority feeling arises from a sense of imperfection mental motivating him to be better.